Andesites and evolution of the continental crust: Perspectives from the Central Volcanic Zone of the Andes - Burns, Dale H.; de Silva, Shanaka L. (Frontiers in Earth Science, 2023)
1. Department of Geological Sciences, Stanford University, Stanford, CA 94503 2. College of Earth, Oceanic, and Atmospheric Sciences, Oregon State University, Corvallis, OR 97331 Abstract During the past 10 Myr andesites from the Central Andes record the production of two distinct types of andesite that correspond with major geodynamic changes in the Central Volcanic Zone (CVZ). Major composite cones and small centers associated with the Quaternary CVZ arc have trace element and isotopic characteristics consistent with a magma generation/fractionation in the lower crustal. Within the Quaternary arc centers, there are also significant latitudinal variations that correspond with the age and composition of the lower crust. In contrast, 6-1 Ma andesites from ignimbrites and lava domes associated with the peak of the regional flare-up have compositions and isotopic signatures that suggest these andesites are hybrids between mantle-derived basalts and upper crustal lithologies. Younger lava domes (<1 Ma) associated with the regional flare-up are compositionally indistinguishable from proximal Quaternary arc centers and thus represent a waning stage of the flare-up and a return to the steady-state magmatism characteristic of the arc. The transition from upper crustal to lower crustal andesite production results from a decrease in mantle heat input and subsequent relaxation of the regional geotherm during the waning of the flare-up event. The two modes of andesite production have significant implications for the production and evolution of the CVZ arc crust. During the flare-up prodigious amounts of basalt were emplaced into the mid-crust resulting in the production of large volumes of hybrid intermediate magmas in the mid and upper crust. In contrast, the lower crustal fractionation recorded in the Quaternary arc andesites would result in the formation of a dense crystalline residue in lower crust and an overall “densification” of the lower crust. Over time, gravity instabilities associated with this densification may ultimately aid in the delamination of the dense lower crustal root, and the triggering of future flare-ups. These differences in andesite production may help to explain the cyclicity (flare-up cycles) observed in mature continental arcs.